2021
DOI: 10.2147/rmhp.s278231
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Integrated Community Case Management Service and Associated Factors Among Mothers/Caregivers Who Have Sick Eligible Children in Southern Ethiopia

Abstract: Background Proper utilization of integrated community case management service has a significant contribution in reducing the under-five children mortality. However, the utilization of integrated community case management service is low especially in developing countries like Ethiopia. Therefore, this study was planned to assess the utilization of integrated community case management service and associated factors among mother/caregivers who have sick children aged 2–59 months in Boloso Sore Woreda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…Caregivers who had heard about ICCM services were 3.7 times more likely to use them than those who had not heard about them. This finding was supported by a study done in the Dara District, UNICEF literature, 13 , 26 south Ethiopia, Boloso Sore Woreda 22 , and Hadiya zone. 23 …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Caregivers who had heard about ICCM services were 3.7 times more likely to use them than those who had not heard about them. This finding was supported by a study done in the Dara District, UNICEF literature, 13 , 26 south Ethiopia, Boloso Sore Woreda 22 , and Hadiya zone. 23 …”
Section: Discussionsupporting
confidence: 61%
“… 21 The probable reasons may be the difference in mode of service delivery, access of services. In contrast to this higher ICCM utilization than studies done in a study conducted in south Ethiopia, Boloso Sore Woreda (25%), 22 Southern Ethiopia, Hadiya zone (22.5%), 23 siraleone (14%), 18 Uganda (27.3%), 9 and Ghana (30%). 24 This difference might be due to access, time, place, and social context variation between this study and previous studies.…”
Section: Discussionmentioning
confidence: 56%
“…The finding of this study is higher than other studies conducted in Ethiopia. For instance the service coverage in Boloso Sore Woreda, Wolaita zone is 25.3% ( 17 ), 22.5% in Hadiya zone ( 20 ), and 10.6% in Kindo Didaye district, Wolaita zone, Southern Ethiopia ( 21 ). The possible reason for the higher utilization of ICCM service in the current study includes the government effort to scale the program at the grassroot level communities through the health extension program.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that when caretakers observe the danger signs such as fever and fast breathing, they were more likely to visit health facilities and utilize ICCM. Congruently, studies conducted in Southern Ethiopia ( 17 ), Dawro Zone, South-west Ethiopia ( 28 ), Oromia, Ethiopia ( 29 ), Kenya ( 30 ), and India ( 31 ) have revealed that the mother's/caregiver's perception of the high severity of illness is associated with of integrated community case management service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation